Clinical Characteristics of Turkish Women with Candida krusei Vaginitis and Antifungal Susceptibility of the C. krusei Isolates - Ahmet Bariş Güzel; Merve Aydın; Melda Meral; Ayşe Kalkancı; Macit Ilkit (Hindawi Limited, 2013)
Objective. Candida krusei causes approximately 1% of vulvovaginal candidiasis (VVC) cases and is naturally resistant to fluconazole. Antifungal testing may be required if C. krusei vaginitis fails to respond to non-fluconazole therapy, particularly in patients with recurrent infections. Design. We investigated the clinical characteristics and antifungal susceptibility profile of vaginal C. krusei isolates. Between 2009 and 2012, we identified 560 unrelated Candida spp.-positive vaginal cultures, of which 28 (5.0%) were C. krusei. These isolates were analyzed according to host factors and the clinical forms of VVC, and their in vitro susceptibility to 10 antifungal agents was tested using a reference microdilution method. Results. We observed that perineal laceration and increased age (>50 years) were significant predictors of C. krusei in vaginal samples (P<0.05). All isolates were susceptible to amphotericin B, caspofungin, ketoconazole, and miconazole. Additionally, susceptible dose-dependent and resistant rates were found for fluconazole as 42.9% and 57.1%, respectively. Remarkably, only 42.9% and 67.9% of the isolates were susceptible to itraconazole and voriconazole, respectively. Conclusions. Understanding local susceptibility patterns, especially those of non-C. albicans Candida species, can significantly aid in the selection of an effective antifungal agent. The in vivo response of C. krusei vaginitis to various antifungal therapeutics remains unknown and requires further research.